PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 5 TANJUNG PUNAK - Kasibah, Kasibah; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is dilator by the low of learning result of class V SDN 5 Tanjung Punak in math subjects. Can be seen from the Minimum Criteria of Completeness (KKM) defined by the school that is 65, from 21 students of class V that reach KKM is 9 students (42,86%) and who do not reach KKM is 12 students (57,14%) with average class 60,81. The purpose of this research is to improve student learning outcomes of grade V SDN 5 Tanjung Punak with the application of cooperative learning model type numbered heads together. This study presents the learning results obtained from Daily Deuteronomic values before the action with an average of 60.81 increased to 73.57 in cycle I, and increased again to 77.61 in cycle II. Teacher activity in the first cycle of the first meeting is 50% with sufficient criteria, the second meeting with a value of 70.83% with good criteria. In cycle II first meeting, teacher activity is 75% with good criterion, and at second meeting is 83,33% with very good criterion. Student activity on first cycle of first meeting is 37,5% with less criterion, second meeting is 70,83% with good criterion. In cycle II first meeting, student activity is 75% with good category, and at second meeting is 83,33% with criteria very good. Based on the results of this study, it can be proven that the application of cooperative learning model numbered heads together type can improve student learning outcomes of grade V SDN 5 Tanjung Punak.Keywords: numbered heads together, mathematics learning result